2018
DOI: 10.1007/s10916-018-0956-z
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Improve Communication and Reduce Physician Stress and Burnout in a University Affiliated Residency Program

Abstract: Ineffective communication between nursing staff and residents leads to numerous educational and patient-care interruptions, increasing resident stress and overall workload. We developed an innovative and simple, secure electronic health record (EHR) base text paging system to communicate with internal medicine residents. The goal is to avoid unnecessary interruption during patient care or educational activities and reduce stress. Traditional paging system can send a phone number to call back. We developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…Similar studies found the EHR messaging system to improve resident's stress and satisfaction levels. 1 We did see a slight trend in improvement, but our results were not statistically significant. We believe that burnout is a complex topic with multiple factors and that decreasing the number of interruptions might not be enough to significantly decrease physician burnout to cause a statistically significant result.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Similar studies found the EHR messaging system to improve resident's stress and satisfaction levels. 1 We did see a slight trend in improvement, but our results were not statistically significant. We believe that burnout is a complex topic with multiple factors and that decreasing the number of interruptions might not be enough to significantly decrease physician burnout to cause a statistically significant result.…”
Section: Discussioncontrasting
confidence: 56%
“…Evolving technological advances have proven to be an intricate part of health care interdisciplinary communication systems. Ineffective communication between nursing staff and residents or physicians leads to numerous educational and patient care interruptions, increasing stress and overall workload 1 . Studies have shown that lack of control over work organization is one of the stressors for residents that may contribute to burnout 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…64e68 All 3 studies with interventions evaluating EHR improvements significantly improved satisfaction and decreased stress (Table 2). 64,65,67 With the exception of Menachemi et al, 66 interventions of EHR implementation in a workflow generally worsened or had no effect on burnout or its indicators. 59,60,63,66,68 Trends identified within these studies included perceived insufficient training contributed to EHR ineffectiveness; EHR use by the physician within clinic visits negatively impacted patient-centered communication; and physician characteristics associated with less satisfaction included older age (>55 years), male sex, and surgical specialties.…”
Section: Teamworkmentioning
confidence: 99%
“…Despite the importance of stress in the lives of individuals (Moore et al, 2016) and specifically in the case of university students (Lapointe et al, 2018), and the role played by EI as well as self-efficacy in the said stress, few studies have simultaneously analyzed the role played by both aspects as regard stress (Aguilar et al, 2014). In response to this, the present research aims to determine the role played by self-efficacy and EI over perceived stress.…”
Section: Introductionmentioning
confidence: 99%